2012
DOI: 10.1261/rna.033423.112
|View full text |Cite
|
Sign up to set email alerts
|

A dominant role for meiosis-specific 3′ RNA processing in controlling expression of a fission yeast cyclin gene

Abstract: Meiotic gene regulation provides a rich source of insight into mechanisms of temporal control during development. We previously reported that accumulation of many meiotic mRNAs in fission yeast is governed by changes in 39 RNA processing and elucidated the molecular basis of this regulatory mechanism for an early meiotic gene. Here, we report that cleavage/polyadenylation is also the nexus of negative control for middle meiotic genes. Parallel profiles of splicing and polyadenylation are observed over a meioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(159 reference statements)
0
3
0
Order By: Relevance
“…A subset of meiotic genes in S. pombe was also shown to undergo APA upon meiosis induction, and it was suggested to be important for the regulation of their expression (McPheeters et al 2009;Cremona et al 2011;Potter et al 2012). The mechanisms involved are discussed in a following paragraph.…”
Section: Apa Regulation Of Meiotic Gene Expressionmentioning
confidence: 97%
See 1 more Smart Citation
“…A subset of meiotic genes in S. pombe was also shown to undergo APA upon meiosis induction, and it was suggested to be important for the regulation of their expression (McPheeters et al 2009;Cremona et al 2011;Potter et al 2012). The mechanisms involved are discussed in a following paragraph.…”
Section: Apa Regulation Of Meiotic Gene Expressionmentioning
confidence: 97%
“…Even though the ratio between the short and the long isoforms slightly changes during the time course of meiosis, the distal PAS is always more predominantly used over the proximal PAS (McPheeters et al 2009;Chen et al 2011). Later studies identified additional meiotic transcripts using meiosis specific 3 0 processingdependent regulation (Cremona et al 2011;Potter et al 2012). These transcripts were found to utilize more than one PAS upon meiosis induction, but again in this case the proximal PAS usage relatively to the distal PAS was not studied in detail.…”
Section: Apa Regulation Of Meiotic Gene Expressionmentioning
confidence: 99%
“…We demonstrate that in the absence of the Integrator complex, Spt5 plays a central role in restricting non-coding transcription, possibly representing an ancient mechanism to control transcription within the non-coding genome. Therefore, we propose that Spt5/4 plays a role in restricting transcriptional output from promoters of lowly expressed genes such as non-coding genes that are also supressed by the post-transcriptional mechanisms 109,112,[131][132][133][134] .…”
Section: Spt5 Is Required For Restricting Non-coding Transcription An...mentioning
confidence: 99%